Learning and experiencing ryptography with cryptool and sagemath / by Bernhard Esslinger - Esslinger, Bernhard Esslinger (Norwood : Artech House, 2024)
This book provides a broad overview of cryptography and enables cryptography for trying out. It emphasizes the connections between theory and practice, focuses on RSA for introducing number theory and PKI, and links the theory to the most current recommendations from NIST and BSI. The book also enables readers to directly try out the results with existing tools available as open source. It is different from all existing books because it shows very concretely how to execute many procedures with different tools. The target group could be self-learners, pupils and students, but also developers and users in companies. All code written with these open-source tools is available. The appendix describes in detail how to use these tools. The main chapters are independent from one another. At the end of most chapters, you will find references and web links. The sections have been enriched with many footnotes. Within the footnotes you can see where the described functions can be called and tried within the different CrypTool versions, within SageMath or within OpenSSL.
Includes appendix, references and index
Keywords: Elliptic curve cryptography; Symmetric key cryptography; Public key cryptography